Oral biofilms - Al-Ahmad, Ali (Monographs in oral science / series editors A. Lussi, M.A.R. Buzalaf, 2021)
Biofilms are highly organized polymicrobial communities that are embedded in an extracellular matrix and formed on natural and artificial surfaces. In the oral cavity, biofilms are formed not only on natural teeth, but also on restorative materials, prosthetic constructions, and dental implants. Oral diseases like caries, gingivitis, periodontitis, and also pulp inflammation are associated with biofilms. This publication is an up-to-date overview on oral biofilms from different clinically relevant perspectives. Experts comprising basic researchers and clinicians report on recent research relating to biofilms - from general summaries to recommendations for daily clinical work. This book covers all aspects of oral biofilms, including models used in the laboratory, biofilms in dental water unit lines, periodontal and peri-implant biofilms, caries-related biofilms, halitosis, endodontic biofilms, and Candida infections, as well as biofilms on dental materials and on orthodontic appliances. Several chapters deal with anti-biofilm therapy, from the efficacy of mechanical methods and the use of antimicrobials, to alternative concepts. This publication is particularly recommended to dental medicine students, practitioners, other oral healthcare professionals, and scientists with an interest in translational research on biofilms.